(3GdNdGUI GdfGaYI HGdCOdI GdbGWYI aj ahGFO GdJGHYIs - (3CHh GdMSf CMeO Hf GdMSjf Hf eMeO Hf CHj HcQ GdQUGU GdUfYGfjs
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg (B: (3hgh GdEeJfGY ef GdaYd eY GdbOQg Ydjg , hGdeONd gh GdJCKjQ s
(3BNQgG (B:s
(3hbGd Udi Gddg Ydjg hBdg (B: (3GdYde YdeGf (B: (3Yde HGddSGf gh GdMLI Ydjc , hYde HGdbdH gh GdfGaY dc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3Ydi MhGTi GdfSNI HYV GdJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJhMjO hGdedd hGdfMds